Prevalence, Risk Factors, and Maternal Outcomes of Polycystic Ovary Syndrome (PCOS) in Reproductive-Age Women. A Cross-Sectional Study - Areeba Ayub, Sajida Imran, Afshan Mushtaq, Moizza Aziz, Fouzia Jan, Hanana Hameed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Polycystic Ovary Syndrome (PCOS) is a common endocrine disorder among women of reproductive age, associated with a spectrum of metabolic, reproductive, and psychological complications. Despite growing recognition of its clinical significance, regional data on its prevalence, associated risk factors, and maternal health outcomes remain limited. Objective: To determine the prevalence of PCOS, identify associated risk factors, and evaluate its impact on maternal outcomes in reproductive-age women. Methodology: This cross-sectional study included 100 women aged 18 to 45 years attending tertiary care gynecology clinics. PCOS was diagnosed using the Rotterdam criteria. Data were collected on demographic characteristics, clinical features, biochemical markers, and maternal health parameters including fertility status, gestational complications, and mode of delivery. Results: The prevalence of PCOS in the study population was 36%. Significant risk factors included obesity (p = 0.003), family history of PCOS (p = 0.001), and insulin resistance (p = 0.004). Women with PCOS had higher incidences of subfertility (48% vs. 21%, p = 0.01), gestational diabetes mellitus (29% vs. 10%, p = 0.02), and cesarean delivery (41% vs. 24%, p = 0.03) compared to non-PCOS women. Conclusion: PCOS is highly prevalent among reproductive-age women and is significantly associated with adverse maternal outcomes. Early detection and targeted management strategies are essential to reduce reproductive and metabolic complications. Keywords: Polycystic Ovary Syndrome, Prevalence, Risk Factors, Maternal Outcomes, Cross-Sectional Study, Reproductive Health.